Perlindungan Konsumen Atas Kerugian Akibat Ulasan Menyesatkan Pada Produk Barang Di E-Commerce - Abdillah, Rayhan Fajar; Handono, Mardi; Kusuma, Ajeng Pramesthy Hardiani (PT Matra Cendikia Abadi, 2025)
Over time, problems have arisen for consumers when shopping online. One of these problems is the prevalence of misleading reviews attached to products offered by businesses on E-Commerce platforms. The widespread use of misleading reviews is certainly very detrimental to consumers who want to shop online, as consumers will not obtain accurate information that corresponds to the benefits of the products they intend to buy. The legal research method used in this study is the normative juridical research method with the use of statutory and conceptual approaches. This study has two main discussions, namely the forms of consumer protection and the legal efforts that consumers can take against losses resulting from misleading reviews spread on E-Commerce platforms. In accordance with the main issues discussed, this study analyzes and examines how legal protection is obtained by consumers, both internally sourced from agreements and externally sourced from applicable laws and regulations, as well as how dispute resolution efforts can be pursued by consumers through both litigation and non-litigation methods.